2015
DOI: 10.1152/japplphysiol.00023.2015
|View full text |Cite
|
Sign up to set email alerts
|

High dietary sodium reduces brachial artery flow-mediated dilation in humans with salt-sensitive and salt-resistant blood pressure

Abstract: Recent studies demonstrate that high dietary sodium (HS) impairs endothelial function in those with salt-resistant (SR) blood pressure (BP). The effect of HS on endothelial function in those with salt-sensitive (SS) BP is not currently known. We hypothesized that HS would impair brachial artery flow-mediated dilation (FMD) to a greater extent in SS compared with SR adults. Ten SR (age 42 ± 5 yr, 5 men, 5 women) and 10 SS (age 39 ± 5 yr, 5 men, 5 women) healthy, normotensive participants were enrolled in a cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 40 publications
1
32
0
Order By: Relevance
“…These studies are summarized in Table . The outcomes examined were diverse: one study assessed mortality outcomes (category I), two studies assessed morbidity outcomes (category II), two studies assessed outcomes related to symptoms/quality of life/functional status (category III), six studies assessed BP outcomes (category IV), seven studies assessed other clinically relevant surrogate outcomes (category V), and 10 studies assessed physiologic outcomes (category VI) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies are summarized in Table . The outcomes examined were diverse: one study assessed mortality outcomes (category I), two studies assessed morbidity outcomes (category II), two studies assessed outcomes related to symptoms/quality of life/functional status (category III), six studies assessed BP outcomes (category IV), seven studies assessed other clinically relevant surrogate outcomes (category V), and 10 studies assessed physiologic outcomes (category VI) …”
Section: Resultsmentioning
confidence: 99%
“…No primary research studies in the physiologic category (category VI) met the minimum methodological criteria. A range of outcomes were captured by the studies considered to be of lower quality, including all‐cause mortality, headaches/migranes, BP, cognitive function, acne, obesity and ghrelin, multiple sclerosis, BMD, gastric cancer, flow‐mediated dilatation, pulse wave velocity, markers of the renin‐angiotensin‐aldosterone system, heart rate, insulin resistance and the metabolic syndrome, brain tissue white matter hyperintensity, uric acid, and urinary albumin . Most of these studies found adverse effects of dietary salt on health, except for three that were neutral and one that found an inverse relationship between salt intake and headaches/migranes …”
Section: Resultsmentioning
confidence: 99%
“…Women lay supine for~20 -30 min, and a venous blood sample was obtained from an antecubital vein to assess sex steroids and plasma ET-1. Conduit artery endothelial function was assessed in the brachial artery using FMD as previously described (11,37). Briefly, a longitudinal image of the brachial artery was obtained via ultrasound (GE P5; Healthcare, Waukesha, WI).…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Another secondary analysis was performed to determine whether individuals classified as “salt-sensitive” had impaired nocturnal dipping during the HS diet. Salt-sensitivity was defined as a 5 mmHg or more change in 24h mean arterial pressure from LS to HS, as previously described (22). Ten participants were classified as salt-sensitive (Δ mean arterial pressure = 9±1 mmHg).…”
Section: Resultsmentioning
confidence: 99%